State of the art: What have the pain sciences brought to physiotherapy? - Romy Parker; Victoria J. Madden (AOSIS, 2020)
Background: Pain is the most common reason for patients to seek help from a health care professional. In the past few decades, research has yielded gains in the Pain Sciences - multiple fields of scientific research that, when integrated, help to clarify what causes and influences human pain. Objectives: In this article, we discuss the key areas in which the Pain Sciences have shifted the physiotherapy profession. Method: A narrative review of the Pain Sciences literature was conducted. The review analyses how the Pain Sciences have influenced physiotherapy in several categories: assessment; clinical reasoning; treatment; research rigor and building the profile of the profession. Results: Scientific research on pain has largely converged in support of three 'game-changing' concepts that have shifted the physiotherapy profession's understanding and treatment of pain: (1) pain is not a signal originating from bodily tissues, (2) pain is not an accurate measure of tissue damage and (3) the plasticity of the nervous system means the nervous system itself is a viable target of treatment. These three concepts have influenced physiotherapy assessment and treatment approaches, and research design to consider pain mechanisms using patient-centred models. Conclusion: The Pain Sciences have shifted physiotherapists' assessment and treatment approaches and shifted the status of the physiotherapy profession. Ultimately the Pain Sciences have embedded interdisciplinary teams and expanded physiotherapy practice. Clinical implications: We believe that the pain sciences should be embedded in undergraduate and postgraduate education and training of physiotherapists (including the three key concepts regarding pain) to benefit physiotherapists and their patients.